Effects of KRN4884, a Novel K+ Channel Opener, on Ionic Currents in Rabbit Femoral Arterial Myocytes - Katsuhiko Muraki; Akiko Sasaoka; Susumu Ohya; Minoru Watanabe; Yuji Imaizumi (Elsevier, 2003)
ABSTRACT: Effects of KRN4884 (5-amino-N-[2-(2-chlorophenyl)ethyl]-N'-cyano-3-pyridinecarboxamidine), a novel K+ channel opener, on ionic currents were examined in rabbit femoral arterial myocytes (RFAMs). Under whole-cell clamp conditions where cells were superfused with 5.9 mM K+ bathing solution, KRN4884 elicited an outward current at -30 mV. KRN4884-induced current had a reversal potential of -78 mV and was abolished by application of glibenclamide (glib). KRN4884 was approximately 43 times more potent than levcromakalim in activating an ATP-sensitive K+ current (IK-ATP). On the other hand, KRN4884 affected neither voltage-dependent Ca2+ nor delayed rectifier K+ channel currents. In the inside-out patch clamp configuration where cells were superfused with the symmetrical 140 mM K+ solution, KRN4884 activated 47 pS K+ channels in the presence of adenosine diphosphate. Similar 47 pS K+ channels, which were reversibly inhibited by glib, were recorded under outside-out patch conditions. Using RT-PCR analysis, we found that inward rectifier K channel 6.1 (Kir6.1) and sulfonylurea 2B (SUR2B) transcripts were predominantly expressed in rabbit femoral artery. These results indicate that KRN4884 potently activates IK-ATP in RFAMs. The KRN4884-sensitive 47 pS K+ channel activity underlying IK-ATP is a vascular type KATP channel consisting of Kir6.1 and SUR2B and has similar characteristics to those of ATP-sensitive K+ channels activated by K+ channel openers in other types of smooth muscles.